2017
DOI: 10.1007/s10552-017-0919-6
|View full text |Cite
|
Sign up to set email alerts
|

Trichomonas vaginalis infection and risk of prostate cancer: associations by disease aggressiveness and race/ethnicity in the PLCO Trial

Abstract: Purpose Results from previous sero-epidemiologic studies of Trichomonas vaginalis infection and prostate cancer (PCa) support a positive association between this sexually transmitted infection and aggressive PCa. However, findings from previous studies are not entirely consistent, and only one has investigated the possible relation between T. vaginalis seropositivity and PCa in African-American men who are at highest risk of both infection and PCa. Therefore, we examined this possible relation in the Prostate,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 29 publications
3
32
0
Order By: Relevance
“…Lastly, if we view our findings in the context of prostate disease development rather than prostate involvement, our nonsignificant findings are in line with those from a growing body of studies that observed null associations between T. vaginalis serostatus and prostate cancer risk and aggressiveness in older men, as well as those from one, but not the other, previous study of T. vaginalis serology and BPH. However, our findings are not consistent with the high prevalence of T. vaginalis DNA and antigens observed in prostate tissue from older men with BPH …”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Lastly, if we view our findings in the context of prostate disease development rather than prostate involvement, our nonsignificant findings are in line with those from a growing body of studies that observed null associations between T. vaginalis serostatus and prostate cancer risk and aggressiveness in older men, as well as those from one, but not the other, previous study of T. vaginalis serology and BPH. However, our findings are not consistent with the high prevalence of T. vaginalis DNA and antigens observed in prostate tissue from older men with BPH …”
Section: Discussionsupporting
confidence: 89%
“…Viewing our findings in the context of the longer‐term or cumulative influences of current and/or resolved infections rather than the acute influences of infection, our nonsignificant findings are consistent with those from previous cross‐sectional studies of nonlifelong infections ( T. vaginalis and syphilis) that observed null associations with PSA, but differ from those from other cross‐sectional and longitudinal studies that observed positive findings for C. trachomatis serostatus and histories of medical record–confirmed chlamydia and NCNGU diagnoses with PSA concentration and trajectories in younger men . However, in the latter study, positive associations were observed only when PSA trajectories were examined and not when only one PSA measurement was used (% with PSA ≥0.7 ng/mL = 38.3 for chlamydia, 39.6 for gonorrhea, and 31.7 for NCNGU vs 37.1 for controls without these infections; P = 0.772, 0.639, and 0.659, respectively).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In males, trichomoniasis is mostly asymptomatic; however, it is associated with a higher risk of aggressive prostate cancer (Marous et al. ).…”
mentioning
confidence: 99%
“…Moreover, the infection is associated with a higher risk of HIV transmission, cervical cancer, and preterm birth and higher rates of mortality in newborn babies (Dionne-Odom et al 2018;Feng et al 2018;Nanda et al 2006;Petrin et al 1998;Rendon-Maldonado et al 2003). In males, trichomoniasis is mostly asymptomatic; however, it is associated with a higher risk of aggressive prostate cancer (Marous et al 2017).…”
mentioning
confidence: 99%